2012
DOI: 10.1074/jbc.m112.394932
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Cholera Toxin Production by Anaerobic Respiration of Trimethylamine N-oxide in Vibrio cholerae

Abstract: Background: The human intestine, in which Vibrio cholerae exerts its virulence, is an anaerobic environment. Results: When grown anaerobically with trimethylamine N-oxide (TMAO), V. cholerae exhibited enhanced growth and cholera toxin (CT) production was remarkably induced. Conclusion: Anaerobic TMAO respiration may serve as a signal to increase V. cholerae virulence. Significance: A novel growth condition that induces CT production is uncovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 55 publications
(59 reference statements)
1
69
0
Order By: Relevance
“…Recently, we reported that CT production was remarkably induced when V. cholerae was grown anaerobically using trimethylamine N-oxide (TMAO) as an alternative electron acceptor (11). CT production was not observed when the anaerobic growth was stimulated by other alternative electron acceptors, such as fumarate, DMSO, and nitrate (11), demonstrating the specific effect of TMAO on the anaerobiosis-induced CT production in V. cholerae.…”
mentioning
confidence: 99%
“…Recently, we reported that CT production was remarkably induced when V. cholerae was grown anaerobically using trimethylamine N-oxide (TMAO) as an alternative electron acceptor (11). CT production was not observed when the anaerobic growth was stimulated by other alternative electron acceptors, such as fumarate, DMSO, and nitrate (11), demonstrating the specific effect of TMAO on the anaerobiosis-induced CT production in V. cholerae.…”
mentioning
confidence: 99%
“…␤-Galactosidase activity assays were performed as described previously (7). posable element and a mariner C9 transposase (28).…”
Section: Methodsmentioning
confidence: 99%
“…The 500-bp flanking sequences located at both ends that were used to introduce the mutation were amplified by PCR with the primers listed in Table 2. Construction of a chromosomal P VC1589 ::lacZ transcriptional fusion was performed as described previously (7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22] Moreover, hypoxia or anoxia is used as a signal not only to trigger changes in expression of genes that allow adaptation to the lack of oxygen but also upregulate the activity of genes that result in obvious damaging consequences for the cell: they encode toxins. 23 Perhaps it would not be surprising to learn that bacterial pathogens use perturbations of their membrane(s) induced by certain offensive external stimuli not only as a signal to elicit appropriate responses to maintain the integrity of the cell envelope ('envelope stress response', ESR) but also to mobilise components of their pathogenic armoury, as such distress may be interpreted as a signal that they have encountered hostile elements of the host immune system. Moreover, perturbations of the bacterial cell envelope may be selfinflicted and can occur through the assembly and/or activity of protein secretion systems.…”
mentioning
confidence: 99%